2008
DOI: 10.1007/s00404-008-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periodontal status and preterm low birth weight delivery: a case–control study

Abstract: The extent and severity of periodontal diseases appeared to be associated with increased odds of PLBW delivery. Nevertheless, more and larger intervention trials are needed before it can be fully accepted that periodontal infection is a true risk factor for PLBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 18 publications
7
52
1
3
Order By: Relevance
“…Different associations between periodontal status and preterm birth alone (PB), low birth weight (LBW), or preterm birth associated to low birth weight (PLBW) have been shown in cross-sectional studies (29)(30)(31)(32)(33)(34)(35)(36), as well as in casecontrol studies (37,38). However, other cohort studies (36,(39)(40)(41), as well as case-control studies (17,(42)(43)(44)(45), did not find a significant association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different associations between periodontal status and preterm birth alone (PB), low birth weight (LBW), or preterm birth associated to low birth weight (PLBW) have been shown in cross-sectional studies (29)(30)(31)(32)(33)(34)(35)(36), as well as in casecontrol studies (37,38). However, other cohort studies (36,(39)(40)(41), as well as case-control studies (17,(42)(43)(44)(45), did not find a significant association.…”
Section: Discussionmentioning
confidence: 99%
“…Različite povezanosti između paradontnog statusa i PVPa, niske porođajne težine, ili prijevremenog porođaja povezanog s niskom porođajnom težinom, opisane su u presječnim istraživanjima (29 -36) te u istraživanjima kontroliranih slučajeva (37,38). Ipak, u drugim istraživanjima (36, 39 -41) i istraživanjima kontroliranih slučajeva nije pronađena značaj-na povezanost.…”
Section: Raspravaunclassified
“…Positive associations between periodontal status and preterm birth alone, low birth weight or preterm birth associated to Low Birth Weight (PLBW) have been reported by cohort/cross-sectional studies by Offenbacher et al, Jeffcoat MK et al, 7 Lunardelli and Peres, 26 Gomes-Filho et al 27 and Khader et al 28 Similarly, there is no consensus regarding the benefit of dental therapy preventing preterm birth in the form of scaling and root planing during pregnancy in the literature. A meta-analysis of RCTs done by Polyzos et al 29 in 2009 showed that treatment resulted in significantly lower preterm birth and borderline significantly lower low birth weight.…”
Section: Discussionmentioning
confidence: 93%
“…Support for maternal periodontal disease acting as a significant risk factor for PLBW births has been established by numerous studies (Khader et al, 2009;Offenbacher et al, 1996;Moliterno et al, 2005 (Boggess et al, 2005;McGaw, 2002;Vergnes and Sixou, 2007). Hormonal change during gestation is also believed to promote gum inflammation causing destructive oral diseases like gingivitis and periodontitis (Siristatidis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%